Profil Kadar Kolesterol Total dan Trigliserida Berdasarkan Usia dan Jenis Kelamin terhadap Risiko Kardiovaskular - Lusti, Nur Fara; Yusuf, Arfina; Gunawan, I Agus Adi (Jurnal Sains Farmasi Dan Kesehatan, 2026)
Heart disease is a leading cause of morbidity and mortality worldwide. Elevated total cholesterol and triglyceride levels are major risk factors influenced by age and gender. Therefore, analyzing lipid profiles based on demographic characteristics is important for cardiovascular risk assessment. This study aimed to analyze total cholesterol and triglyceride levels based on age and gender as indicators of cardiovascular disease risk. This descriptive study involved 41 respondents. The variables analyzed included age, gender, total cholesterol levels, and triglyceride levels. Total cholesterol levels were classified as normal (<200 mg/dL) and abnormal (≥200 mg/dL), while triglyceride levels were classified as normal (<150 mg/dL) and abnormal (≥150 mg/dL). Data were analyzed descriptively and presented as distribution tables and percentages. The results showed that 70.7% of respondents had abnormal total cholesterol levels, while 75.6% had normal triglyceride levels. Higher total cholesterol and triglyceride levels tended to occur in the 40–59 year age group. Both male and female respondents showed proportions of abnormal lipid levels that may increase cardiovascular risk. In conclusion, abnormal lipid profiles are still commonly found and may contribute to increased cardiovascular disease risk.